Pelatihan Sumber Daya Manusia terhadap Produktivitas Kinerja Karyawan di UPT PBAT Sukorejo - Diva Mabila; Tsalis Elfina Roudhotul Jannah; M. Yusuf Azwar Anas (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
Human resources are an important aspect in running a business because quality human resources can produce significant results. Productivity is a key factor for the success of a business, with high productivity providing benefits for the company and employees. Therefore, entrepreneurs and company employees must strive to increase their productivity. Efforts to increase productivity include employee training and development, because improving individual quality can help overcome weaknesses and also improve skills which can ultimately be utilized optimally. In the context of an organization, human resource management places a high priority on employee training and development. The aim of this research is to disseminate the impact of human resource training on employee performance productivity at UPT PBAT SUKOREJO. This research uses a qualitative descriptive approach by applying the Interactive Analysis Model data analysis technique developed by Mills and Huberman. The research results show that the implementation of human resource training on employee performance productivity at UPT PBAT SUKOREJO is carried out optimally through participation in training programs provided by the organization.Keywords: Training, Performance, Productivity